2011
DOI: 10.1039/c0nr00990c
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic etching for fabrication of flexible and all-solid-state micro supercapacitor based on MnO2 nanoparticles

Abstract: Micro-supercapacitors are a promising candidate whose reliability and performances are struggling to meet the energy demands dictated by the incoming generation of miniaturized electronic devices. In this paper, we describe a facile and low-cost method for fabricating flexible and all-solid-state micro supercapacitors by microfluidic etching. The micro-supercapacitor configuration is composed of sub-10-nm-scale MnO(2) nanoparticle interdigital microelectrode fingers prepared by microfluidic etching with H(3)PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 33 publications
1
91
0
1
Order By: Relevance
“…From a materials perspective, carbon is earth abundant and inexpensive; hence, many nanostructured carbon-based materials have been studied for use in electric double-layer (EDL) micro-supercapacitors, including activated carbons 4 , carbon nanotubes 5 , carbide-derived carbons 1,6 and onion-like carbon 2 . In addition, transition metal oxides such as ruthenium oxide 7 and manganese oxide 8 , and conducting polymers such as polypyrrole 9 and polyaniline 10 have been used as materials for pseudo-capacitive micro-supercapacitors. Among all the previous examples, only onion-like carbon has produced a microsupercapacitor with ultrahigh-power handling with an RC time constant of only 26 ms (ref.…”
mentioning
confidence: 99%
“…From a materials perspective, carbon is earth abundant and inexpensive; hence, many nanostructured carbon-based materials have been studied for use in electric double-layer (EDL) micro-supercapacitors, including activated carbons 4 , carbon nanotubes 5 , carbide-derived carbons 1,6 and onion-like carbon 2 . In addition, transition metal oxides such as ruthenium oxide 7 and manganese oxide 8 , and conducting polymers such as polypyrrole 9 and polyaniline 10 have been used as materials for pseudo-capacitive micro-supercapacitors. Among all the previous examples, only onion-like carbon has produced a microsupercapacitor with ultrahigh-power handling with an RC time constant of only 26 ms (ref.…”
mentioning
confidence: 99%
“…[ 13,20,28 ] Here, we propose a modifi ed novel 3D interdigital electrode structures (as shown in Figure 6 ) to enhance the performance of supercapacitors in order to meet the practical demands and simplify the fabrication technique to facilitate the industrial production. All the procedures were carried out by low-cost industrial equipment with very simple steps, which was demonstrated in the previous text.…”
Section: Resultsmentioning
confidence: 99%
“…In the pioneering work by Xue et al, [152] a thin layer of MnO 2 nanofiber film was first deposited by electrospinning, which was then transferred onto gel electrolyte and sputtered with an ITO layer. In the pioneering work by Xue et al, [152] a thin layer of MnO 2 nanofiber film was first deposited by electrospinning, which was then transferred onto gel electrolyte and sputtered with an ITO layer.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%